Development of a Physics Learning Model Based on Ecopedagogy Approach to Foster Disaster Mitigation Awareness - Hamdi Hamdi; Muhammad Saiful; Muchsin Muchsin (Postgraduate, University of Mataram, 2024)
Climate change has drastically increased natural disasters, with Indonesia ranking third among disaster-prone countries. This research aims to develop a learning model to build disaster mitigation awareness through education. The study focuses on Pidie Regency, Aceh, an area prone to various natural disasters including earthquakes, tsunamis, and volcanic eruptions. The research employs a Research and Development design using the Plomp model, consisting of five phases: investigation, design, realization/construction, test/evaluation/revision, and implementation. The result is the Ecopedagogy Rescue (EcoRescue) learning model, which enables students to explore and discover information about disaster issues and mitigation efforts. Validation scores indicate that the EcoRescue model is valid, with 87.5% for design and 91% for content. The effectiveness score based on teacher responses reached 86.4%, categorizing the model as highly effective in physics education. This study's novelty lies in developing an ecopedagogy-based learning model incorporating disaster mitigation content. The research recommends physics teachers to implement the EcoRescue model in high school physics courses, aiming to enhance students' awareness and understanding of disaster mitigation in their local context